1998
DOI: 10.1073/pnas.95.15.8963
|View full text |Cite
|
Sign up to set email alerts
|

NaN, a novel voltage-gated Na channel, is expressed preferentially in peripheral sensory neurons and down-regulated after axotomy

Abstract: Although physiological and pharmacological evidence suggests the presence of multiple tetrodotoxinresistant (TTX-R) Na channels in neurons of peripheral nervous system ganglia, only one, SNS͞PN3, has been identified in these cells to date. We have identified and sequenced a novel Na channel ␣-subunit (NaN), predicted to be TTX-R and voltage-gated, that is expressed preferentially in sensory neurons within dorsal root ganglia (DRG) and trigeminal ganglia. The predicted amino acid sequence of NaN can be aligned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
306
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 468 publications
(325 citation statements)
references
References 59 publications
(72 reference statements)
19
306
0
Order By: Relevance
“…7) could result from the effect of cyclic GMP on TTX-R I Na rather than K ATP . However, TTX-R sodium channels are expressed in ∼80% of the small diameter sensory neurons (Novakovic et al 1998;Dib-Hajj et al 1998). If the actions of cyclic GMP were on TTX-R I Na only, then we would have expected to encounter ∼80% of the neurons to be sensitive to the inhibitory effects of cyclic GMP whereas we found that the sensitization produced by PGE 2 was reversed by 8-Br cyclic GMP in ∼50% of the small to medium diameter neurons (11 of 21).…”
Section: Discussionmentioning
confidence: 72%
“…7) could result from the effect of cyclic GMP on TTX-R I Na rather than K ATP . However, TTX-R sodium channels are expressed in ∼80% of the small diameter sensory neurons (Novakovic et al 1998;Dib-Hajj et al 1998). If the actions of cyclic GMP were on TTX-R I Na only, then we would have expected to encounter ∼80% of the neurons to be sensitive to the inhibitory effects of cyclic GMP whereas we found that the sensitization produced by PGE 2 was reversed by 8-Br cyclic GMP in ∼50% of the small to medium diameter neurons (11 of 21).…”
Section: Discussionmentioning
confidence: 72%
“…Tetrodotoxin-resistant voltage-dependent sodium channels Nav1.8 (SNS) and Nav1.9 (NaN or SNS2) are selectively expressed in small/medium-sized nociceptive neurons and contribute to the production of an action potential in these neurons. In addition, functional studies reveal that Nav1.8 and Nav1.9 have a specialized role in mediating pain [1,2,[15][16][17]. Thus, the level of gene expression and/or distribution of these channels may be altered in aging neurons that have lowered sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The second step is initiation of action potentials in the nociceptors by voltage-gated sodium channels (VGSCs). Among the 10 VGSC isoforms, two, Na v 1.8 (Akopian et al, 1996;Sangameswaran et al, 1997) and Na v 1.9 (Dib-Hajj et al, 1998;Tate et al, 1998), are expressed almost exclusively by small nociceptor primary afferent neurons (Amaya et al, 2000) and are tetrodotoxin insensitive. Na v 1.8 generates a tetrodotoxin-resistant (TTXr) current with a threshold of activation of Ϫ40 mV that inactivates slowly (TTXrSlow) (Akopian et al, 1996;Sangameswaran et al, 1997;Renganathan et al, 2002b;John et al, 2004), whereas Na v 1.9 is presumed from recordings in Na v 1.8 null mice, to produce a persistent current with a more hyperpolarized voltage dependence and ultraslow recovery from inactivation (TTXr-Per) Baker et al, 2003).…”
Section: Introductionmentioning
confidence: 99%